Suppressing Alopecurus myosuroides in winter cereals by delayed sowing and pre-emergence herbicides - Roland Gerhards; Miriam H. Messelhäuser; Bernd Sievernich (Plant, Soil and Environment, 2022)
Delayed sowing of winter cereals in Western Europe is a preventive method to reduce Alopecurus myosuroides infestations. Two series of on-farm studies including 36 experiments were conducted in South-Western Germany to analyse the combined effects of delayed sowing and pre-emergence herbicide application on A. myosuroides density, weed control efficacy and cereal grain yield. From 2006 until 2009, pendimethalin + flufenacet was applied one week after sowing winter barley and winter wheat. From 2018 until 2020, cinmethylin was used in winter wheat and winter triticale. Densities of A. myosuroides in the untreated early sown control plots amounted up to 1 233 plants/m2. Delayed sowing on average reduced densities by 43%. The mixture of pendimethalin + flufenacet in combination with delayed sowing controlled 87% of the A. myosuroides plants and increased cereal grain yields from 6.4 t/ha in the early sown untreated control to 7.9 t/ha. Cinmethylin in combination with delayed sowing resulted in 91% weed control efficacy and increased grain yields from 5.3 t/ha to 8.8 t/ha. Average grain yields of all delayed sowing treatments were 0.7 t/ha higher than in the early sown treatments. Therefore, delayed sowing combined with pre-emergence herbicide application is a cost-effective strategy of integrated weed management (IWM) in winter cereals reducing dependency on post-emergence herbicide use and mitigating the risk of herbicide resistance development.